A study of the fluoride content of the different infant formulas available in Metro Manila - Ofilada, Edmund Julian L.; Racela, Benjamin F.; Mabanta, Carina Z. (Adviser).
Nine infant formulas were tested for their fluoride content using the fluoride ion selective electrode method. All infant formulas were found to contain insufficient amount of fluoride to meet the minimum daily requirement for infants (0.25 mg F per day) with Prosobee having the highest reading (0.108 mg F per day) and Alacta the lowest (0.003 mg F per day).
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Fluorides